A comparative study of the police code of silence: Exploring the relation between the code of silence and societal characteristics. Issue 2 (17th January 2020) - Kutnjak Ivković, Sanja; Haberfeld, Maria; Kang, Wook; Peacock, Robert Patrick; Porter, Louise E.; Prenzler, Tim; Sauerman, Adri
Abstract : Purpose: The purpose of this paper is to explore the contours of the police code of silence, a critical component of the ability to control misconduct and enhance integrity within any police agency. Unlike the extant research, dominated by single-country studies, this paper provides an in-depth exploration of the code across five countries and tests the relation between the code of science and societal characteristics. Design/methodology/approach: A police integrity survey was used to measure the contours of the code of silence among police officers in Australia ( n =856), Croatia ( n =966), South Africa ( n =871), South Korea ( n =379) and the USA ( n =664). The respondents evaluated 11 hypothetical scenarios describing various forms of police misconduct. Findings: Bivariate analyses reveal considerable divergence in the code of silence across the five countries. Multivariate models of the code of silence show that, next to organizational factors (i.e. the respondents' assessment of peers' willingness to report, evaluations of misconduct seriousness and expected discipline) and individual factors (i.e. supervisory status), societal factors (i.e. the Corruption Perceptions Index score and the percent of irreligious citizens) are significant predictors of the respondents' willingness to report. Research limitations/implications: While the same questionnaire was used in all five countries, the nature of the data collection differed somewhat across the countries (e.g. online survey vs paper-and-pencil survey), as did the nature of the samples (e.g. representative sample vs convenience sample). Practical implications: Perceived peer pressure, measured as the perceptions of whether other police officers would adhere to the code of silence, is the key variable explaining the police officers' expressed willingness to adhere to the code of silence. Changing the police officers' perceptions of peer culture and potentially changing the peer culture itself should be critical elements in the toolbox of any administrator willing to curtail the code of silence. Originality/value: Whereas the study of the code of silence has started several decades ago, no prior study has tested the effects of organizational and societal variables on the code of silence in a comparative perspective.